EFFECT OF TRAINING PLIOMETRIC IN KARATE PRACTITIONERS (Fiep Bulletin - online, 2014)
This research had as focus to analyze karate under the vision of the porting training being verified the effect of the pliometric training in this modality. The present study it had as objective to verify if the pliometric training would increase the power of members in the practitioners of karate. The sample is composed for a group of 12 intermediate practitioners of karate with age between 18 and 28 years in three academies in Rio De Janeiro. The individuals had been divided in two groups, with 6 elements each one, the group and group B. Had a feminine element in each one of the groups. The groups had been submitted the tests of muscular power. After the accomplishment of the test the group was submitted It the eight weeks of pliometrics training three times per week, while group B submitted it eight weeks of resistance training and force with the weight of the proper body, also three times per week. It was used adeseiva ribbon, chair, rope, metric trena and medicine ball of three kilos. Inquiry is concluded after an improvement in the muscle power of MMII in the group submitted to the superior pliometric training the improvement obtained for the group that did not use this training. Soon the pliometric training probably is advisable for the practitioners of snshou that they desire to improve its muscle power of MMII. However, the same he was not evidenced for the MMSS, where the group that used exercises of resistance and force with the weight of the proper body had obtained a expressivo result. Of this form the study it suggests that this method of training more is indicated for the practitioners of sanshou that they long for an improvement in the muscular power of MMSS.
Keywords: Pliometric training; Karate; muscle Power